Photonic Integrated Gain Switched Optical Frequency Comb for Spectrally Efficient Optical Transmission Systems - M. Deseada Gutierrez Pascual; Vidak Vujicic; Jules Braddell; Frank Smyth; Prince Anandarajah; Liam Barry (IEEE Photonics Journal)
We demonstrate the performance of a novel integrated gain switched optical frequency comb source (GS-OFCS) in two different optical transmission systems. The device generates a 6.25-GHz frequency spaced comb that comprises eight spectral tones in a 3-dB spectral power ripple. The GS-OFCS presents good noise properties, which include relative intensity noise of ${\sim -}$ 125 dB/Hz and linewidth of 1.5 MHz. We then employ the device in two transmission systems that use advanced modulation formats. First, it is employed in a four-level pulse amplitude modulation format system operating at 3.125-GBaud per channel and over 3 km of standard single mode fiber (SSMF), where all the channels performed below the 7% FEC limit and the receiver sensitivity achieved was $-$ 21 dBm. Then, the GS-OFCS is used in a Nyquist quadrature phase-shift keying (QPSK) system at 5-Gbaud per channel and over 50 km of SSMF, where all the channels exhibited a similar performance well below the 7% FEC limit. These results, in conjunction with the compactness and cost efficiency of the integrated device, denote the quality and relevancy of the resultant comb source for future optical transmission systems.